ANALISIS PERBANDINGAN PENGGUNAAN GRI INDEKS DAN ISR INDEKS DALAM PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN PERBANKAN INDONESIA TAHUN 2010 - 2013 - Vena Gustian; Faisal Faisal (Diponegoro Journal of Accounting, 2015)
This study aims to measure the level of disclosure of the social responsibility activities in Indonesian banking based on the index of each type of banking. The index used in this study are GRI (Globar Reporting Initiative) for conventional banking and ISR (Islamic Social Reporting) for Islamic banking. The study also measured the difference social responsibility disclosure between conventional banking and Islamic banking. A four-year span between 2010 to 2013 is used to look at the pattern of social responsibility disclosure every year. The population in this study is the entire banking that existed in Indonesia. As many as 32 conventional banking and 11 Islamic banking being the object of this study. Data collection method is study documentation using the annual report of each banking between 2010 to 2013. Mann Whitney U-test was used to test the hypothesis in this study. The results show that the pattern of social responsibility disclosure between conventional banking and Islamic banking is different. Conventional banking get the fluctuations in their social responsibility disclosure, while Islamic banking is always increasing. The results of the Mann Whitney U-test also showed that the level of social responsibility disclosure of Islamic banking is better than conventional banking